Malnutrition Risk Factors In TBC: A Case Study In Medan, Indonesia - Ritonga, Imelda Liana (Universitas Aisyah Pringsewu, 2020)
The purpose of the study was to discuss the causes of malnutrition in TB patients: A case study in Medan Indonesia, this research method is a case study from Luck, Jackson and Usher (2005), the results of this study are the factors that cause malnutrition in TB patients found from this study. are (1) elderly and pre-elderly TB patients, (2) TB patients with Diabetes Mellitus, (3) TB patients with HIV, (4) TB patients with treatment failure. The data from this study indicate the need for an assessment of the nutritional status of patients when TB is diagnosed. This is to increase awareness of the nutritional status of the patient since the patient was diagnosed with TB. In accordance with the results of this study, the assessment really needs to be emphasized in cases of TB with the elderly, TB with HIV, TB with Diabetes Mellitus and TB with treatment failure.Abstrak: Tujuan penelitian untuk membahas penyebab malnutrisi pada pasien TB: Studi kasus di Medan Indonesia, metode penelitian ini adalah studi kasus dari Luck, Jackson and Usher (2005), hasil penelitian ini adalah faktor-faktor penyebab malnutrisi pada pasien TB ditemukan dari penelitian ini. adalah (1) pasien TB lansia dan pra-lansia, (2) pasien TB dengan Diabetes Mellitus, (3) pasien TB dengan HIV, (4) pasien TB dengan kegagalan pengobatan. Data dari penelitian ini menunjukkan perlunya penilaian status gizi pasien saat didiagnosis TB. Hal ini untuk meningkatkan kesadaran akan status gizi pasien sejak pasien terdiagnosis TB. Sesuai dengan hasil penelitian ini, pengkajian sangat perlu ditekankan pada kasus TB dengan usia lanjut, TB dengan HIV, TB dengan Diabetes Mellitus dan TB dengan kegagalan pengobatan.